Indirect comparisons of new oral anticoagulant drugs for efficacy and safety when used for stroke prevention in atrial fibrillation - Lip, Gregory Y H; Larsen, Torben Bjerregaard; Skjøth, Flemming; Rasmussen, Lars Hvilsted (Journal of the American College of Cardiology, 2012)
This study sought to perform an indirect comparison analysis of dabigatran etexilate (2 doses), rivaroxaban, and apixaban for their relative efficacy and safety against each other. Data for warfarin compared against the new oral anticoagulants (OACs) in large phase III clinical trials of stroke prevention in atrial fibrillation (AF) are now available for the oral direct thrombin inhibitor, dabigatran etexilate, in 2 doses (150 mg twice daily [BID], 110 mg BID), and the oral Factor Xa inhibitors, rivaroxaban and apixaban. A "head-to-head" direct comparison of drugs is the standard method for comparing different treatments, but in the absence of such head-to-head direct comparisons, another alternative to assess the relative effect of different treatment interventions would be to perform indirect comparisons, using a common comparator. Nonetheless, any inter-trial comparison is always fraught with major difficulties, and an indirect comparison analysis has many limitations, especially with the inter-trial population differences and thus, should not be overinterpreted. Indirect comparison analysis was performed using data from the published trials. There was a significantly lower risk of stroke and systemic embolism (by 26%) for dabigatran (150 mg BID) compared with rivaroxaban, as well as hemorrhagic stroke and nondisabling stroke. There were no significant differences for apixaban versus dabigatran (both doses) or rivaroxaban; or rivaroxaban versus dabigatran 110 mg BID in preventing stroke and systemic embolism. For ischemic stroke, there were no significant differences between the new OACs. Major bleeding was significantly lower with apixaban compared with dabigatran 150 mg BID (by 26%) and rivaroxaban (by 34%), but not significantly different from dabigatran 110 mg BID. There were no significant differences between apixaban and dabigatran 110 mg BID in safety endpoints. Apixaban also had lower major or clinically relevant bleeding (by 34%) compared with rivaroxaban. When compared with rivaroxaban, dabigatran 110 mg BID was associated with less major bleeding (by 23%) and intracranial bleeding (by 54%). There were no significant differences in myocardial infarction events between the dabigatran (both doses) and apixaban. Notwithstanding the limitations of an indirect comparison study, we found no profound significant differences in efficacy between apixaban and dabigatran etexilate (both doses) or rivaroxaban. Dabigatran 150 mg BID was superior to rivaroxaban for some efficacy endpoints, whereas major bleeding was significantly lower with dabigatran 110 mg BID or apixaban. Only a head-to-head direct comparison of the different new OACs would fully answer the question of efficacy/safety differences between the new drugs for stroke prevention in AF.